Anti-cancer Therapies Employing IL-2 Cytokine Tumor Targeting: Contribution of Innate, Adaptive and Immunosuppressive Cells in the Anti-tumor Efficacy - Mortara, Lorenzo; Balza, Enrica; Bruno, Antonino; Poggi, Alessandro; Orecchia, Paola; Carnemolla, Barbara (Frontiers in Immunology, 2018)
Antibody-cytokine fusion proteins (immunocytokines) exert a potent anti-tumor effect by specific antibodies and delivering cytokines to the immunesuppressive tumor microenvironment (TME). Once bound to the tumor target, immunocytokines composed by antibody or single chain Fv conjugated with interleukin-2, can promote the in situ recruitment and activation of effector immune cells, such as natural killer (NK) and cytotoxic T lymphocytes (CTL). This recruitment induces a TME switch towards a classical T helper 1 (TH1) anti-tumor immune response, supported by the crosstalk between NK and dendritic cells (DC). Furthermore, some IL-2 immunocytokines have been largely shown to trigger tumor cell killing by antibody dependent cellular cytotoxicity (ADCC), through Fcγ receptors engagement. The modulation of the TME can be also achieved with immunocytokines conjugated with a mutated form of IL-2 that impairs regulatory T (Treg) cell proliferation and activity. IL-2 immunocytokine administration can overcome the severe toxicities of the systemic administration of high doses of soluble unconjugated IL-2, as demonstrated in preclinical animal models and more recently in phase I/II clinical trials. Promising results have been reported using IL-2 immunocytokines delivered in combination with other immunocytokines, chemo-, radio-, anti-angiogenic therapies, and blockade of immune checkpoints. Here, we summarize and discuss the most relevant reported studies with a focus on the effects of IL-2 immunocytokines on innate and adaptive anti-tumor immune cell responses as well as immunosuppressive Treg cells and approaches to circumvent its severe toxic side effects.